Alterações inflamatórias no tecido adiposo visceral e músculo esquelético em ratos wistar obesos exógenos frente ao protocolo de treinamento aeróbico e/ou intervenção dietética - Costa, Jean Lucas Fernandes da (Universidade Federal de São Carlos, 2022)
Obesity is a disease that has a multifactorial etiology that can lead to the triggering of several other diseases such as hypertension, atherosclerosis and diabetes. In addition, the expansion of adipose tissue has led to harmful consequences not only in this tissue, but in a systemic way. In this sense, the search for strategies that reduce body adiposity, such as physical exercise and dietary interventions, have been investigative targets in several studies. Thus, this study aimed to determine the concentrations of inflammatory markers in visceral adipose tissue and skeletal muscle, to verify changes in body mass and adipocyte size in obese rats after continuous moderate-intensity training (MICT) and/or dietary intervention. After eight weeks of obesity induction through the consumption of a palatable high-fat diet (HFD), twenty male Wistar rats were divided into four groups: control rats fed with HFD (HFD-SED); obesity rats fed with HFD and submitted to MICT (HFD-MICT); obesity rats that were submitted to a nutritional intervention by switching HFD to chow-diet (CD-SED); and obesity rats that were submitted to MICT and nutritional intervention by switching HFD to chow-diet (CD-MICT). All animals in the training groups were submitted to MICT with an intensity of 50-80% of Vmax, three times a week, for 8 weeks. The gastrocnemius muscle (GAST) and mesenteric adipose tissue (mWAT) were collected to quantify TNF-α, IL-6 and IL-10 through enzyme-linked immunosorbent assay (ELISA). Additionally, retroperitoneal (rWAT) and epididymal (eWAT) adipose tissue were collected and weighed. The body mass was recorded before and after the experimental protocol and mWAT adipocyte morphology was assessed using histological analysis. The results showed that the HFD-SED presented higher body mass, higher concentrations of inflammatory markers in mWAT and an increase in adipocyte size and other obesity parameters. The CD-SED and CD-MICT groups showed reductions in body mass, relative weight of visceral fat deposits, adipocyte area of mWAT, and increased maximal exercise capacity. Furthermore, there was a reduction in the concentrations of TNF-α, IL-6 and IL-10 in these groups in mWAT, but not in GAST. In addition, the CD-MICT group showed high values for the IL-10/TNF-α ratio in mWAT. Finally, we conclude that an eight-week dietary intervention independently or associated with MICT are effective in reducing some of the deleterious effects caused by obesity.
Inflammatory changes in visceral adipose tissue and skeletal muscle in exogenous obese wistar rats in front of aerobic training protocol and/or dietary intervention
Keywords: Marcadores inflamatórios; Tecido adiposo visceral; Músculo esquelético; Treinamento contínuo de intensidade moderada; Intervenção dietética; Obesidade exógena; Dieta hiperlipídica palatável; Inflammatory markers; Visceral adipose tissue; Skeletal muscle; Moderate intensity continuous training; Dietary intervention; Exogenous obesity; High-fat diet; CIENCIAS BIOLOGICAS::FISIOLOGIA